SOSIALISASI KELUARGA PADA KENAKALAN REMAJA DI DESA LEMITO UTARA KECAMATAN LEMITO KABUPATEN POHUWATO - Dewinta Rizky R. Hatu; Rahmatiah Rahmatiah; Abd. Halid Lemba; Giwang Eka Putri Suaib (Jurnal Ilmiah Sosiologi Agama (JISA), 2026)
The main focus of this study is to examine the role of family socialization as the primary agent in shaping adolescent behavior and its relationship with juvenile delinquency in rural communities. This study aims to analyze the process of socialization within the family and the factors influencing juvenile delinquency in North Lemito Village, Lemito District, Pohuwato Regency. This study employed a qualitative method with a descriptive approach to gain an in-depth understanding of family interaction dynamics and adolescent behavior within a social context. Data were collected through observation, interviews, and documentation techniques, with informants selected using purposive sampling, including parents, adolescents, and community leaders. The data analysis technique used an interactive model consisting of data reduction, data presentation, and conclusion drawing. The findings revealed that family socialization has not been carried out optimally, as reflected in the lack of open communication between parents and children, inconsistent parental supervision, and ineffective instillation of moral and religious values. In addition, environmental factors such as peer influence, alcohol consumption, and weak social control within the community further contributed to juvenile delinquency. Therefore, this study emphasizes that the family plays an essential role as the primary socialization agent in preventing juvenile delinquency, highlighting the need to strengthen communication, supervision, and value inculcation within the family in a sustainable manner.